Modulation of the Corticomotor Excitability by Repetitive Peripheral Magnetic Stimulation on the Median Nerve in Healthy Subjects - Jia, Yanbing; Liu, Xiaoyan; Wei, Jing; Li, Duo; Wang, Chun; Wang, Xueqiang; Liu, Hao (Frontiers in Neural Circuits, 2021)
Abstract Objective: We aimed to examine the effects of repetitive peripheral nerve magnetic stimulation on the excitability of the contralateral motor cortex and motor function of the upper limb in healthy subjects. Methods: Forty-six healthy subjects were randomly assigned to either a repetitive peripheral nerve magnetic stimulation group (n = 23) or a sham group (n = 23). The repetitive peripheral nerve magnetic stimulation group received stimulation using magnetic pulses at 20 Hz, which were applied on the median nerve of the non-dominant hand, whereas the sham group underwent the same protocol without the stimulation output. The primary outcome was contralateral transcranial magnetic stimulation-induced corticomotor excitability for the abductor pollicis brevis of the stimulated hand in terms of resting motor threshold, slope of recruitment curve, and peak amplitude of motor evoked potentials, which were measured at baseline and immediately after each session. The secondary outcomes were motor hand function including dexterity and grip strength of the non-dominant hand assessed at baseline, immediately after stimulation, and 24 h post-stimulation. Results: Compared with the sham stimulation, repetitive peripheral nerve magnetic stimulation increased the peak motor evoked potential amplitude immediately after intervention. The repetitive peripheral nerve magnetic stimulation also increased the slope of recruitment curve immediately after intervention and enhanced hand dexterity after 24h. However the between group difference for the changes were not significant. The significant changes in hand dexterity and peak amplitude of motor evoked potential after repetitive peripheral nerve magnetic stimulation were associated with their baseline value. Conclusions: Repetitive peripheral nerve magnetic stimulation may modulate the corticomotor excitability together with a possible lasting improvement in hand dexterity, indicating that it might be helpful for clinical rehabilitation.